Diffusion in nanocrystalline solids - Chadwick, Alan V. (Diffusion Fundamentals, 2005)
Enhanced atomic migration was an early observation from experimental studies into nanocrystalline solids. This contribution presents an overview of the available diffusion data for simple metals and ionic materials in nanocrystalline form. It will be shown that enhanced diffusion can be interpreted in terms of atomic transport along the interfaces, which are comparable to grain boundaries in coarse-grained analogues. However, the method of sample preparation is seen to play a major role in the experiments and there are still many gaps in understanding the detailed mechanisms of diffusion in these systems.